HUBUNGAN INTENSITAS MENONTON TAYANGAN KEKERASAN DI TELEVISI TERHADAP PERILAKU BULLYING PADA REMAJA - Dahniel " Darwis; Fathra Annis Nauli; Safri " " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
ABSTRACT Bullying was often case among adolescents. One of the factors that lead to bullying behavior in adolescents was often watch violence on television. This study aimed to examine the relationship between the intensity of watching violence on television against bullying behavior in adolescents. This research used descriptive research design correlation with cross sectional approach. The research sample numbering 93 respondents taken based on inclusion criteria using proportionate stratified random sampling technique and using chi square test. The results showed that the majority of respondents was 17 years (65.6), high bullying behavior as much (58.1), and the intensity of watching violence on television is in the category often as many (51.6). The statistical results between the intensity of watching violence on television against bullying behavior obtained p value (0.000) <alpha (0.05) so that it can be concluded there is a significant correlation between the intensity of watching violence on television against bullying behavior. The results of this study recommend teenagers to choose the types of impressions that can be watched on television so that bullying behavior can be avoided. Keywords: bullying, the intensity of watching, teen, impressions violence